Skaldic Poetry across Borders. Sigvatr Þórðarson’s Austrfararvísur - Maria Cristina Lombardi (Lea)
The Austrfararvísur (Verses on a Journey to the East) could be defined as a poem of borders: in these vísur Sigvatr Þórðarson, the skald of Óláfr the Saint, narrates his crossing of various geographical, political, and religious borders. Austrfararvísur are preserved in Snorri Sturluson’s Óláfs saga helga and concern the famous episode of Sigvatr’s visit to Västergötland, where he attempted to mediate a peace deal between King Óláfr Haraldsson of Norway and the king of Sweden. The text describes dramatic moments and inhospitable places that Sigvatr experienced in his travel from Norway to Sweden, where an immense forest still serves as a natural border today. This was also the natural border that the Norwegian dynasty traversed when, in prehistoric times, Swedish kings moved from Sweden to Norway. Now Sigvatr follows the same path, but in the opposite direction.